(untitled) (Journal of Engineering, 2023)
A roundabout is a highway engineering concept meant to calm traffic, increase safety, reduce stop-and-go travel, reduce accidents and congestion, and decrease traffic delays. It is circular and facilitates one-way traffic flow around a central point. The first part of this study evaluated the principles and methods used to compare the capacity methods of roundabouts with different traffic conditions and geometric configurations. These methods include gap acceptance, empirical, and simulation software methods. Previous studies mentioned in this research used various methods and other new models developed by several researchers. However, this paper’s main aim is to compare different roundabout capacity models for acceptable capacity predictions for single-lane and multi-lane roundabouts. In conclusion, previous studies such as RODEL, SIDRA, Swiss, HCM6, and IRC overestimate capacity, while the GHCM method underestimates it. Each VISSIM and SIDRA predicted higher capacity than HCM2010, Paramics, and Simtrafic capacity methods. Generally, the precise prediction of capacity value depends on the circulating flow, exiting traffic flow, driver behavior, and geometric variations. Also, a comparison between seventeen methods was made using virtual data. For a single-lane roundabout, Girabase and Swiss models estimated higher capacity values when compared with other models, while HCM 2010 estimated lower capacity. The Shamueli’s model provides an estimate of capacity about the same as the lower bound of the HCM 2000 model. Brilon’s model estimated lower capacity values for a multi-lane roundabout compared with other methods. At low circulating flow, the Girabase model estimated a higher capacity value, while with the increasing circulating flow, the FHWA2000 estimated a higher capacity than the Girabase model. Also, there is a bit of a difference between SIDRA 5 and 8.0. There is a small interval between models that are implemented in a single-lane roundabout. Therefore, the models are better at predicting the capacity of a single lane than they are at predicting the capacity of multiple lanes.